Male Versus Female Leaders: The Effect of Leader Need for Dominance on Follower Satisfaction - Bartol, Kathryn M. (Academy of Management Journal, 1974)
The stereotype of the dominant female leader who adversely affects the satisfaction of subordinates is tested utilizing a simulated business task. In general, satisfaction data for five different aspects of the situation do not support the view that high need for dominance female leaders have a detrimental effect on subordinate satisfaction.